(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article provides a scientific and theoretical analysis of the artistic interpretation of social issues in children’s literature. It reveals the educational and aesthetic functions of children’s literature and explains how social problems are expressed in a form adapted to children’s psychology—simple in presentation yet profound in meaning. Based on examples from Uzbek children’s literature, particularly the works of Gafur Ghulam, Khudoyberdi Tokhtaboyev, and Anvar Obidjon, the article analyzes the artistic representation of such social issues as compassion, orphanhood, injustice, poverty, labor education, and social responsibility. Through excerpts from literary works, the impact of social problems on a child’s consciousness and their educational significance is substantiated.